Exercise plasma boosts memory and dampens brain inflammation via clusterin - De Miguel, Zurine; Khoury, Nathalie; Betley, Michael J.; Lehallier, Benoit; Willoughby, Drew; Olsson, Niclas; Yang, Andrew C.; Hahn, Oliver; Lu, Nannan; Vest, Ryan T.; Bonanno, Liana N.; Yerra, Lakshmi; et al. (Nature (London), 2021)
Physical exercise is generally beneficial to all aspects of human and animal health, slowing cognitive ageing and neurodegeneration 1 . The cognitive benefits of physical exercise are tied to an increased plasticity and reduced inflammation within the hippocampus 2 – 4 , yet little is known about the factors and mechanisms that mediate these effects. Here we show that ‘runner plasma’, collected from voluntarily running mice and infused into sedentary mice, reduces baseline neuroinflammatory gene expression and experimentally induced brain inflammation. Plasma proteomic analysis revealed a concerted increase in complement cascade inhibitors including clusterin (CLU). Intravenously injected CLU binds to brain endothelial cells and reduces neuroinflammatory gene expression in a mouse model of acute brain inflammation and a mouse model of Alzheimer’s disease. Patients with cognitive impairment who participated in structured exercise for 6 months had higher plasma levels of CLU. These findings demonstrate the existence of anti-inflammatory exercise factors that are transferrable, target the cerebrovasculature and benefit the brain, and are present in humans who engage in exercise. Plasma from voluntarily running mice reduces baseline expression of neuroinflammatory genes and experimentally induced brain inflammation when infused into sedentary mice.